Paham Radikal dalam Pandangan Tokoh Agama di Banda Aceh - Rini Marlina; Suraiya IT; Syarifuddin Syarifuddin (Jurnal Pemikiran Islam, 2021)
Radicalism is one of the notions that can damage the social order in society, especially when it comes to religion. This study aims to find out specifically about the understanding of Islamic religious leaders in Banda Aceh City about the teachings and movements of religious radicalism, the factors that influence the development of religious radicalism, and the response of Islamic religious leaders in Banda Aceh City in responding to the development of religious radicalism today. This study uses a qualitative approach and the research method is descriptive. Data collection techniques were carried out by interview, documentation, and literature study. The results of this study indicate that the teachings and movements of radicalism are understood by Islamic religious leaders in Banda Aceh City as an understanding that will change the politics of Muslim and social communities through violence, this perspective is contrary to Islamic values and cannot be tolerated, because the characteristics of This movement tends to blame the other party. Attitudes like blasphemy, loud-speaking style, imposing will on others, like to blame and disbelieve in others. Factors causing radicalism include the lack of understanding about Islam and the country. Politically, certain politicians use religion as a tool to promote themselves to gain power. In addition, this research states that there is incitement and bribery to the community to commit violence for a fee. The Islamic religious leaders of Banda Aceh City responded strongly to the teachings and movements of radicalism by showing an attitude of rejection of the existence of the movement because it was considered contrary to the teachings of religion and the state. This movement can harm other people and damage good relations in the life of the nation, religion, and state.AbstrakRadikalisme merupakan paham yang dapat  menggoyahkan tatanan sosial dalam masyarakat terutama jika berkaitan dengan agama. Penelitian ini bertujuan untuk mengetahui secara khusus tentang pemahaman tokoh agama Islam Kota Banda Aceh tentang ajaran dan gerakan radikalisme agama, faktor yang mempengaruhi perkembangan radikalisme agama dan respon tokoh agama Islam Kota Banda Aceh dalam menyikapi berkembangnya radikalisme agama dewasa ini. Penelitian ini menggunakan pendekatan kualitatif, metode penelitian bersifat deskriptif. Teknik pengumpulan data dilakukan dengan wawancara, dokumentasi dan studi kepustakaan. Berdasarkan hasil penelitian diketahui bahwa ajaran dan gerakan radikalisme dipahami oleh tokoh agama Islam Kota Banda Aceh sebagai suatu paham yang ingin mengadakan suatu perubahan baik secara politik maupun sosial melalui jalan kekerasan, dan ini bertentangan dengan nilai-nilai keislaman. Hal ini tidak dapat ditoleril, karena ciri gerakannya bersifat merugikan pihak lain seperti suka menghujat, gaya bicara yang keras, memaksakan kehendak pada orang lain, suka menyalahkan dan mengkafirkan orang. Faktor penyebab terjadinya radikalisme antara lain minimnya pemahaman mengenai agamanya maupun tentang negaranya. Pada faktor politik oleh para politikus tertentu, memakai agama sebagai benteng untuk mempromosikan dirinya demi kepentingan kekuasaan, adanya hasutan dan penyogokan kepada golongan awam dengan cara dibayar. Para tokoh agama Islam Kota Banda Aceh merespon keras ajaran dan gerakan radikalisme yakni dengan menunjukkan sikap penolakan keberadaan gerakan tersebut karena dianggap bertentangan dengan ajaran agama dan negara. Gerakan ini dapat merugikan orang lain serta merusak hubungan baik kehidupan berbangsa, agama dan negara.